Accounting for geographical variance in the union satisfaction gap. Issue 2 (7th March 2019) - Bryson, Alex; Davies, Rhys
Abstract: Evidence of spatial variance in the relationship between trade union membership and job satisfaction is limited. Using three nationally representative data sets, we examine lower levels of satisfaction among union members and considers how this relationship varies geographically across the nations and regions of Great Britain. The analysis demonstrates that the union satisfaction gap can largely be accounted for by relative characteristics of union members and the jobs that they hold. However, there is evidence of geographical variance. The union satisfaction gap is generally found to be highest within Scotland and North of England. Despite high levels of union membership, evidence of a union satisfaction gap in Wales is relatively weak. These differences relate to differences in the perceptions of industrial relations among employees across these areas, which appear to be related to geographical variance in worker heterogeneity.